(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to measure the impact of energy management with its dimensions (energy planning, monitoring and control systems, preventive maintenance of equipment) on reducing operational costs in petrochemical factories in Yanbu Industrial City. The study adopted the descriptive analytical approach, where a questionnaire consisting of (22) items was designed and distributed to a stratified random sample of (202) respondents from employees at managerial, supervisory, and technical levels involved in energy management, operations, and maintenance in five petrochemical factories. Data were analyzed using simple and multiple linear regression analysis. The results revealed that the level of energy management practices was high with a mean of (3.46), and that all dimensions of energy management have a statistically significant impact at the level (α ≤ 0.05) on reducing operational costs. The combined dimensions of energy management explained (54.9%) of the variance in reducing operational costs. The monitoring and control systems dimension ranked first in terms of impact, followed by energy planning, then preventive maintenance of equipment. The study recommended enhancing investment in smart monitoring systems, developing measurable energy performance indicators, adopting predictive analysis techniques in preventive maintenance, and pursuing ISO 50001 certification to ensure the sustainability of improvement efforts.